DIGNITY AS SEEN IN TENNESSEE WILLIAMS’ A STREETCAR NAMED DESIRE - Tini Mogea; Salaki Reynaldo Joshua (Pusat Riset dan Inovasi Nasional, 2022)
This research is carried out to trace dignity in A Streetcar Named Desire. The dignity is focused on Blanche as a Southern woman, who has a different characterization from her sister Stella. This research is qualitative research since the data are in the form of words and quotations. The data are collected from the drama itself, A Streetcar Named Desire, and other books or references to support the analysis. In analyzing the data, the writer used a mimetic approach. The approach views literature as the imitation and combination of the reality and imagination of the playwright or the result of his imagination that comes from reality. The result shows the existence of the dignity of Blanche as a Southern Woman who lives on wealth and has a plantation in Belle Reve. Blanche’s region and its society have unique values in their social status. It is gentility that includes the manner of treating the caller. Blanche shows that her dignity comes from her cultural and social background as a Southern woman. Blanche serves to symbolize what she felt about the Southern aristocracy as she tries to escape poverty and her reputation although her ancestry is dead. Blanche's struggle with dignity and fantasy serves as one of the main causes of her character’s downfall. Although she puts on a veneer of social snobbery and has a manner that is dainty and frail, in reality, Blanche lies because she refuses to accept the hand fate has dealt her. In the Old South, women depended on men for comfort and status. She is taken away from her dignity. She also desperately clings to and is dragged into a new world of reality and a New South.